GERAKAN LITERASI DINI READHATON SEBAGAI UPAYA MEMBANGKITKAN MEMBACA SISWA DI SEKOLAH ALAM SMP INSAN LITERA - DESA CIHAMPELAS - Wenny Juliati Majid; Sri Nurhayati (Comm-Edu (Community Education Journal), 2020)
This research is backed by a low interest condition of reading communities among children and adolescents in Kp. BBC Village of Cihampelas West Bandung Regency. Especially the students in the junior high School of Insan Litera and any strategy that can be used as an effort to inspire reading. The purpose of this research is (1) to know the strategy to build a community to learn. (2) To know the process of student Readathon activity in Sekolah Alam SMP Insan Litera. The theories used in this research include the concept of community fond of learning, and the concept of Readathon. The method used is a qualitative approach with a descriptive method. Data collection techniques using observation techniques, interviews, and documentation. The location of research in Sekolah Alam SMP Insan Litera which is under the auspices of Bening Saguling Foundation and which is the subject of research is all students of Sekolah Alam SMP Insan Litera, amounting to 11 people, principals, and also representatives of one teacher. Based on the research results that Readathon has carried out well. In this readathon there are several activities carried out consisting of 4 stages of 1) the implementation of Readathon routinely once a week, carried out on Thursday. With the target one student finished reading one book one week. 2) reading book read by PPL students who act as tutors. 3) Discussion of read books packed with fun games or quizzes. 4) Create a geulis tree (literacy Movement) where the student who has completed reading one book writes his name and the title of his book later in the Geulis tree. The condition of learning interest in students is also quite high, visible from students ' participation in following learning programs.